Redesigning the bean seed germination experiment: an activity sheet suggestion. (2nd April 2020) - Ürek, Handan
Abstract: Germinating a seed is presumably the first experiment made by a child in his life. So, it has an important place both in child's scientific experience and understanding. Despite the significance of the experiment, the literature indicates that students possess various misconceptions related to the concepts of seed and seed germination. So, it is thought that this experiment should be focused on in more detail. The purpose of this paper is presenting a proper activity sheet for middle school students to perform this experiment effectively. Science teachers might follow it as an instructional tool in their courses. Thus it is expected to assist students explore the factors which are affective on bean seed germination.